Terapia comunitária integrativa e mulheres vivenciando o climatério:uma pesquisa ação- intervenção - Alves, Estela Rodrigues Paiva (2017)
Integrative Community Therapy (ICT) is a space for welcoming and sharing of life wisdom and suffering experienced in people’s daily lives, where they become therapists of themselves, which enables them to find solutions to their personal and family conflicts. The study was intended to assess the effectiveness of ICT as a health care technology capable of improving self-esteem and mitigating the depression signs and symptoms in women experiencing climacteric. This is an action-research-intervention with 06 women in climacteric who showed depression signs and symptoms and who took part in at least 06 ICT rounds in an Integrated Family Health Unit in João Pessoa-PB, Brazil. Beck’s Depression Inventory and Rosenberg’s Self-esteem Scale – UNIFESP-EPM version were used as instruments, whilst 12 ICT rounds were held as interventions in a 19-week period. In order to produce the empirical material, we used the video-recordings of the rounds, field notebook and semi-structured interviews, which were analyzed through the Bardin thematic content analysis. The study complied with the ethical precepts, and then accepted under the CAAE protocol: 50926615.7.0000.5188. As a result, women have improved self-esteem and mitigated the depression signs and symptoms. We have realized that ICT represented for them a possibility of discovering a new way of seeing life, thus awakening the need for change, through the self-reflection and development of personal skills, such as autonomy, emancipation, empowerment and rescue of self-esteem. We can conclude that ICT is a powerful health care technology capable of enhancing the participants’ standpoint, thus motivating them to leave the stagnation of their lives, by adopting new stances and ways of driving life, as well as encouraging them to reflect and seek answers to their subjective needs, which may entail important changes in their lives.